2013
DOI: 10.1039/c3ra41702f
|View full text |Cite
|
Sign up to set email alerts
|

Examining the base stacking interaction in a dinucleotide context via reversible cyclobutane dimer analogue formation under UV irradiation

Abstract: Substituted tolyl groups are considered as close isosteres of the thymine (T) residue. They can be recognized by DNA polymerases as if they were thymine. Although these toluene derivatives are relatively inert toward radical additions, our recent finding suggests that the dinucleotide analogue TpTo (To = 2'-deoxy-1-(3-tolyl)-β-D-ribofuranose) supports an ortho photocycloaddition reaction upon UV irradiation, producing two cyclobutane pyrimidine dimer (CPD) analogues 2 and 3. Our report here further shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, just like regular CPDs, the CPD formation in TpTo and TpX photoreactions is reversible. 35 Between the two products generated from the TpTo photoreaction, the quantum yield of 1 is 1.7-fold higher than that of 2. Because the outcome of DNA photoreactions is largely determined by the nucleobase stacking conformation before UV excitation, 54,65 the conformer responsible for the formation of 2, in which the toluenyl methyl group may hydrophobically interact with the thymine ring, is 0.11 kJ mol −1 more stable at 77 K than the conformer responsible for the formation of 3.…”
Section: Formation Of Cpd Analogs In the Tpto Photoreaction In Icementioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, just like regular CPDs, the CPD formation in TpTo and TpX photoreactions is reversible. 35 Between the two products generated from the TpTo photoreaction, the quantum yield of 1 is 1.7-fold higher than that of 2. Because the outcome of DNA photoreactions is largely determined by the nucleobase stacking conformation before UV excitation, 54,65 the conformer responsible for the formation of 2, in which the toluenyl methyl group may hydrophobically interact with the thymine ring, is 0.11 kJ mol −1 more stable at 77 K than the conformer responsible for the formation of 3.…”
Section: Formation Of Cpd Analogs In the Tpto Photoreaction In Icementioning
confidence: 97%
“…33 Using an SP-containing oligonucleotide, we solved the first structure of the dinucleotide SP in duplex DNA, and found that SP induces only a minor disturbance of the DNA helical structure. 34 Additionally, using thymine isosteres, we recently extended our studies to the under-standing of the CPD 35,36 and 6-4PP photochemistry, 37 and have gained interesting mechanistic insights into the formation of these two dimers.…”
Section: LImentioning
confidence: 97%
See 1 more Smart Citation